Large capacity multiplex-port brouter with SDH interface for regional PC communication network system - Irie, K.; Ohta, N.; Suto, K.; Morisaki, M.; Tsuji, H. (1997 IEEE International Conference on Communications, 1997)
We have developed a cost-effective regional personal-computer (PC) communication network system based on fiber-to-the-home (FTTH) systems and examined its realization. The system provides a LAN environment and group communication services to the customers. The intelligent bridge circuit, called the low-end card (LEC), is set up in the subscriber's household. The LEC provides the popular Ethernet interface (10Base-T). The leased circuits are connected between the LEC and the center brouter (bridging router). The LEC and the brouter are controlled by the management server to function as the group communication system. The brouter, which has a multiplex subscriber-port interface, is required to accommodate a lot of customers cost effectively. This paper presents the system design of a multiplex-port brouter with SDH/SONET interface. The brouter can accommodate about 2000 subscribers. Ethernet packets are transferred through each subscriber channel between the LEC and the brouter using the HDLC protocol. A group communication mechanism based on packet filtering via the MAC addresses of PCs is presented. The Ethernet packets are filtered by the brouter to eliminate all packets except those from/to the same group members. The implementation of the group management function into the center brouter and the customers premises LEC is discussed. The traffic reduction effect by the brouter is also estimated from experimental results.